Hyaluronidase, acetylcholinesterase inhibiting potential, antioxidant activity, and LC-ESI-MS/MS analysis of polyphenolics of rose (Rosa rugosa Thunb.) teas and tinctures. (18th December 2017) - Olech, Marta; Nowak, Renata; Załuski, Daniel; Kapusta, Ireneusz; Amarowicz, Ryszard; Oleszek, Wieslaw
ABSTRACT: Teas and tinctures prepared from five rose organs were analysed for their antioxidant, anti-hyaluronidase, and acetylcholinesterase inhibiting activity. Moreover, analysis of phenolic acids and flavonoids was carried out by the use of liquid chromatography electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS). As a result, the presence of 10 phenolic acids and 10 flavonoid glycosides was shown. Significant antioxidant potential (0.26 to 4.25 mmol Trolox/g) and reducing power (1092.04 to 9258.70 mmol Fe 2+ /g) was revealed. Moreover, high anti-hyaluronidase activity demonstrated especially by tinctures and differentiated acetylcholinesterase inhibiting effects were observed. The investigated extracts may be considered as potential sources of phenolics and health-promoting ingredients in everyday diet.